2021
DOI: 10.33387/dpi.v10i1.2713
|View full text |Cite
|
Sign up to set email alerts
|

Studi Kasus Kemampuan Representasi Matematis Siswa pada Kelas IX SMP Negeri 2 Telukjambe Timur Kabupaten Karawang

Abstract: Tujuan penelitian ini dilakukan untuk mengkaji kemampuan representasi matematis siswa SMP pada materi lingkaran. Metode penelitian yang digunakan adalah kualitatif dengan desain studi kasus. Subjek penelitian ini adalah 30 siswa kelas IX-A SMP Negeri 2 Telukjambe Timur. Instrumen yang digunakan dalam penelitian yaitu berupa soal uraian sebanyak enam soal, setiap soal mengacu pada indikator kemampuan representasi matematis. Hasil jawaban siswa dianalisis dan dikelompokkan ke dalam kategori dengan kriteria ketun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…However, in general, in learning mathematics, mathematical representations are not used as the main focus (Handayani, 2015;Yuniarti, 2013). Even though mathematical representation abilities are very important in learning mathematics, in reality, students tend to imitate the teacher's steps in solving problems (Athallah & Roesdiana, 2021;Rivaldo, 2021;Silviani et al, 2021;Sri, 2019). As a result, students' representation abilities do not develop, even though mathematical representation is very necessary for learning mathematics for both students and teachers (Ambarwati et al, 2020;Gaffar et al, 2019;Maryati & Monica, 2021;Ulya et al, 2019) However, several studies have found that students' mathematical representation abilities are still relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…However, in general, in learning mathematics, mathematical representations are not used as the main focus (Handayani, 2015;Yuniarti, 2013). Even though mathematical representation abilities are very important in learning mathematics, in reality, students tend to imitate the teacher's steps in solving problems (Athallah & Roesdiana, 2021;Rivaldo, 2021;Silviani et al, 2021;Sri, 2019). As a result, students' representation abilities do not develop, even though mathematical representation is very necessary for learning mathematics for both students and teachers (Ambarwati et al, 2020;Gaffar et al, 2019;Maryati & Monica, 2021;Ulya et al, 2019) However, several studies have found that students' mathematical representation abilities are still relatively low.…”
Section: Introductionmentioning
confidence: 99%